MENGEMBANGKAN MOTORIK KASAR ANAK USIA DINI MELALUI PENDAMPINGAN PERMAINAN ESTAFET BOLA - Nor Ma'rifah; Anida Rahmi; Isnawati; Aghnaita; Saudah; Muzakki (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2022)
The importance of motor-physical development for early childhood needs to be stimulated properly. One of them is through various forms of games that can activate and move children's motor skills. Like a ball relay game that can stimulate children's gross motor development. This community service activity was carried out through the service learning method with a target of 17 students at Yasalmuna Palangkaraya Islamic Kindergarten. The result of this activity is that the child gets gross motor assistance through a ball relay game. Although some children still have difficulty holding the ball and doing other manipulative movements. Therefore, it is necessary to have more varied stimulation activities that can develop children's gross motor skills.